Integrating Educational Games in Problem-Based Learning to Enhance Conceptual Understanding in Mathematics: A Study of Grade VII Students at MTsN 1 Pekanbaru - Devi, Sahra; Widiati, Indah (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This research aims to describe the application of educational games with the Problem Based Learning (PBL) model in the learning process which is aimed at improving students' understanding of mathematical concepts in class VII MTsN 1 Pekanbaru. The basic thinking in this research starts from of mathematical concepts is limited as shown through daily test results data in class VII.5, where only 48.65% of students achieved Essential Graduation Criteria during the learning activities of 87. Research is a The implementation of Classroom Action Research (CAR) took place over two cycles, each of which involved four main steps: preparation, action, observation, and reflection.The research instruments included teacher and student observation sheets and a mathematical concept understanding test. The PBL model was combined with educational game media in the form of traditional games such as snakes and ladders and setatak. A clear improvement is seen inincrease in students' mathematical concept understanding. In cycle I, the percentage of student understanding was in the